Biologics recommendations in the ECCO guidelines on therapeutics in Crohn's disease: medical treatment. Issue 2 (23rd June 2021) - Sriranganathan, Danujan; Segal, Jonathan P; Garg, Mayur
Abstract : In 2019, the European Crohn's and Colitis Organisation released guidelines for the medical management of Crohn's disease, concerning the induction of remission, the maintenance of remission and the treatment of fistulising perianal disease. This review summarises the key recommendations regarding the use of biologics in these settings.